Evaluation of the Buccal Bleeding Time and Platelet Glass Bead Retention as Assays of Hemostasis in the Dog: The Effects of Acetylsalicylic Acid, Warfarin and von Willebrand Factor Deficiency - Brassard, Jacqueline A; Meyers, Kenneth M (Thrombosis and Haemostasis, 1991)
The study evaluated two hemostatic assays in the dog, a modified version of the buccal mucosal bleeding time (BMBT) and the platelet glass bead retention (PR), to describe the aspects of hemostasis measured by these assays. Von Willebrand factor (vWf)-deficient Doberman pinscher dogs were used in evaluating the effects of altered platelet adhesion. Normal dogs were treated with either acetylsalicylic acid (ASA) or warfarin to evaluate the effects of altered platelet aggregation and coagulation. There was significant prolongation of the BMBT and reduction of the PR in vWf-deficient dogs as compared to normal dogs. In ASA treated dogs the BMBT was slightly prolonged; the PR was significantly reduced. The change in ASA-induced BMBT did not correlate with the sensitivity of the dog platelets to arachidonic acid. In warfarin treated dogs there was no change in the BMBT; however, the PR was significantly reduced. The BMBT is a test of hemostasis that is sensitive to platelet adhesion and aggregation deficits. The PR is useful in detecting general abnormalities in hemostasis including platelet adhesion defects due to reduced vWf.